Appendiceal neuroma: an uncommon entity - Jagtap, Sunil V.; Boral, Saswati; Jagtap, Shubham S.; Ajagekar, Pratik D. (International Surgery Journal, 2019)
Appendiceal neuroma or neurogenous hyperplasia of the appendix is an uncommon entity. We report an incidental finding of an appendiceal neuroma in a 35 year male patient who underwent appendectomy. On microscopy showed thickened appendicular wall with well circumscribed submucosal nodules of proliferating spindle cells in myxoid areas, eosinophilic cell infiltration and obliterative appendicitis. It was reported as appendiceal neuroma. We are presenting this case for its uncommon entity, clinical and histopathological finding.